Revitalizing the Meaning of Ta'awun through the Jimpitan Tradition in Addressing Structural Poverty in Rural Indonesia: A Living Qur’an Study: (Revitalisasi Makna Ta'awun melalui Tradisi Jimpitan dalam Pengentasan Kemiskinan Struktural di Pedesaan Indonesia: Studi Living Qur’an) - Kurniawan Ramadhani.; Faisol Nasar bin Madi; H. Abdullah; Mohamad Barmawi (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2025)
The Islamic concept of ta'awun is vital for an ideal social life. In rural Indonesia, jimpitan traditions—forms of Islam-based mutual cooperation—help address economic disparities. The study examines how religious perspectives intersect with cultural practices to enhance financial resilience in the face of poverty in Tugusari Village, Bangsalsari Subdistrict, Jember Regency, East Java. Key challenges include unequal resource distribution and inadequate daily education in Islamic values. This study examines ta'awun using a living Quran approach. It explores the views of community leaders, contextualizes Quranic verses, and assesses the role of ta'awun in poverty alleviation. The research uses the living al-Quran method in a micro-case study, integrating thematic Quranic exegesis, field observations, and in-depth interviews. This contextual method fosters economic resilience. The findings show jimpitan builds social solidarity, teaches resource management, encourages sharing, and reduces poverty through collective zakat and infaq. Jimpitan also fosters community cohesion and promotes Islamic values for sustainable development. Overall, ta'awun through jimpitan demonstrates a successful local, faith-based approach to poverty reduction.